The Students' Representative in the Law Colleges of 14th-Century Damascus - Stewart, Devin (Islamic law and society, 2008)
Abstract This study examines two fatwās issued by Taqī al-Dīn al-Subkī in the mid-14-century regarding the Shāmīyah Madrasah of Damascus. Both texts refer to the position of "representative of the law students" (nāib al-fuqahā) and state that the position had become customary at the Shāmīyah Madrasah and other madrasahs in Damascus during that period. The existence of the post, which has not been noted in scholarship on pre-modern Islamic education to date, shows that madrasah students were more organized in this context than has been realized and raises questions about the institutional character of the madrasah.